Communication Skills as an Enabler to Knowledge Transfer in SMEs - Aziz, Yahya (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2010)
The study was designed to discover the relationship between communication skills and knowledge transfer of engineers in SMEs. The communication skills involved are Listening skills, Seeking and Giving Feedback abilities, Understanding Others abilities ,Influencing and Relating abilities and Oral and Written skills. The findings were collected through a survey by means of questionnaire distributed to subordinates of engineers. The findings show that workers under engineers’ supervision feel that all the communication attributes are important to be possessed by the engineers. However, there is a lack of communication skills in the part of engineers in delivering the knowledge. This, in turn, will affect the receiving of knowledge at the other end. Logically, this will give great impact to the productivity of the companies. This study is a preliminary approach in determining the factors to boost knowledge transfer in industrial sectors. Recommendations are provided to enhance communication skills for better knowledge transfer exercise in organizations.